Standardized acute care doctors training on the emerging pandemic of coronavirus pneumonia - Yadav, Umesh; Kumar, Awan; Yadav, Amrita Kumari; Deo, Ujwal; Yadav, Bimal; Roy, Sanjay; Das, Jyoti; Yadav, Harishankar (Medical Journal of Eastern Nepal, 2022)
The novel corona virus pneumonia epidemic poses a serious challenge to the medical and health systems of all nations in the world, especially discovering the severe shortage of intensive care medical professionals. Although our country’s intensive care medicine physicians have played a primary part in the combat against the epidemic, some problems have been debunked in the training of intensive care medicine personnel; equally there is inadequacy of standardized intensive care medicine training platform, and the lack of integrated training content and training format.Relatively single, insufficient preparations for responding to public health emergencies etc, Based on the actual experience of epidemic prevention and control and the treatment of critically ill patients, this article recommend that standardized training of resident physicians for critical care medicine should be carried out, the training content should be standardized, the combination of theory and clinical practice should be enhanced, the comprehensive quality of resident physicians should be improved, and the training methods should be expanded and strengthened. "Construction of a demand and capacity model for intensive care and hospital". These measures can make the critical care team become a professional team with a feel of social importance, which is of great acceptation for the long-term progress of critical care medicine, for the Nepalese medical system to easily respond to public health emergencies, and improve the comprehensive diagnosis and treatment capabilities of emergency and critical diseases. Excess deaths associated with COVID-19 are a direct result of the inadequate capacity of intensive care units and hospital beds.